The link between psychological-social stress and life style - Šidlauskaitė, Ieva (Psichologija, 2001)
The purposes of this work was to state the connection between psychological-social stress (PS stress) and life style’s features, such as: nicotine use; alcohol use; drugs use; nutrition and physical activity. To state the connection between psychological-social stress level and quantity of nicotine, alcohol, drugs use; tendency to change habits in the direction of healthier life style. Research has been carried according to health questionnaire (translated by A. Gostautas, 2000). For data analysis we used results from common research with 616 youngsters (form 18 till 22 years). Conclusions are following: • Youngsters with higher PS stress level use more cigarettes, alcohol and drugs comparing with youngsters with lover PS stress level. • Youngsters with higher PS stress level are liable not to change using of nicotine, alcohol and drugs, comparing with youngsters with lover PS stress level. • Higher PS stress level is related with unhealthier life style.